Pengaruh Pendidikan Gizi Terhadap Pengetahuan, Sikap Dan Perilaku Konsumsi Pangan Isoflavon Pada Mahasiswi Pre-Menstrual Syndrome - Dhiflatul Frista Anani; Trias Mahmudiono (Amerta Nutrition, 2018)
Background: The age group susceptible to symptoms of Pre-Menstrual Syndrome begins in the early stages of puberty and ends at the menopause stage.The pathophysiology of Pre-Menstrual Syndrome is due to an imbalance of estrogen and progesterone hormones. One of the balancers of both hormones is the consumption of isoflavone food because the structure and its properties resemble estrogen.Objectives: The Purpose of this study was to analyzed the effect of nutritional education on the knowledge, attitude and behavior high food consumption of isoflavone content among female pre-menstrual syndrome.Method: The study was quasy experiment with pre- post control group design. The design of this research was the provision of nutrition education four times for 1 month with duration of each meeting 60 minutes and the provision of soy milk every meeting. The sample technique using simple random sampling total 38 respondents divided into 2 groups (treatment and control group). Preliminary screening to assess PMS using the Shortened Pramenstrual Assessment Form (SPAF) questionnaire. Dependent variable was knowledge, attitude and consumption behavior of isoflavone food, while independent variable was nutrition education.The analysis was performed using Independent t-test.Result: After nutrition education there was significant difference of knowledge and attitude level between treatment and control group respectively p value 0.039 and 0.022. In addition, there were also differences in high food consumption behavior of isoflavone content. The majority of food types are often consumed including: fried tempeh (p = 0.044), tofu (p = 0.036), garlic (p = 0.014) ice soybean milk (p = 0.044) and soybean milk (p = 0.004).Conclusion: Provision of nutrition education to the treatment group can change knowledge, attitude and behavior of high food consumption of isoflavone content, with the existence of increasing consumption behavior, than pre-menstrual syndrome symptoms at student of FKM UNAIR decreased slowly. Although not all types of foods high levels of isoflavones consumed by respondents due to limited time research.ABSTRAKLatar belakang: Kelompok umur yang rentan mengalami gejala Pre-Menstrual Syndrome dimulai pada tahap awal pubertas dan berakhir pada tahap menopause. Patofisiologi Pre-Menstrual Syndrome terjadi karena ketidakseimbangan hormon estrogen dan progesteron. Salah satu penyeimbang kedua hormon yaitu konsumsi pangan isoflavon karena struktur dan sifatnya menyerupai estrogen.Tujuan: Penelitian ini bertujuan untuk untuk menganalisis pengaruh pendidikan gizi terhadap pengetahuan, sikap dan perilakukonsumsi pangan tinggi kadar isoflavon pada mahasiswi dengan premenstrual syndrome.Metode: Penelitian ini merupakan penelitianquasi experiment dengan pendekatan pre-post control group design. Rancang bangun penelitian ini yaitu pemberian intervensi pendidikan gizi 4x pertemuan selama 1 bulan dengan durasi masing-masing pertemuan 60 menit dan pemberian susu kedelai setiap pertemuan. Tehnik sampel menggunakan simple random sampling total 38 responden dibagi menjadi 2 kelompok (kelompok perlakuan dan kontrol). Skrining awal untuk menilai PMSmenggunakan kuesioner Shortened Pramenstrual Assessment Form (SPAF). Variabel dependen adalah pengetahuan, sikap dan perilaku konsumsi pangan isoflavon, sedangkan variabel independen pendidikan gizi. Analisis yang dilakukan menggunakan uji t Independent.Hasil: Setelah diberikan pendidikan gizi terdapat perbedaan signifkan tingkat pegetahuan dan sikap antara kelompok perlakuan dan kontrol dengan nilai p masing-masing 0,039 dan 0,022. Selain itu juga terdapat perbedaan perilaku konsumsi pangan tinggi kadar isoflavon mayoritas jenis makanan sering dikonsumsi meliputi:tempe goreng (p=0,044), tahu (p=0,036), bawang putih (p=0,014) es susu kedelai (p=0,044) dan susu kedelai (p=0,004).Kesimpulan: Pemberian intervensi pendidikan gizi kepada kelompok perlakuan dapat merubah pengetahuan, sikap dan perilaku konsumsi pangan tinggi kadar isoflavon, dengan adanya perilaku konsumsi yang meningkat, maka gejala pre-menstrual syndrome pada mahasiswi FKM UNAIR juga menurun secara perlahan. Walaupun belum semua jenis makanan yang tinggi kadar isoflavon dikonsumsi oleh responden dikarenakan keterbatasan waktu penelitian.